Herbal Therapy in the Management of Polycystic Ovary Syndrome: A Critical Narrative Review of Mechanistic Claims, Clinical Evidence and Translational Barriers - Ayushi Masih; V. Paul (Archives of Current Research International, 2026)
Polycystic ovary syndrome, still widely described as polycystic ovarian disease in parts of South Asia, is the most common endocrine and metabolic disorder affecting women of reproductive age. Its management remains symptom directed, and dissatisfaction with conventional pharmacotherapy has helped make herbal preparations one of the most frequently self-administered adjuncts in this population. The purpose of this critical narrative review is to evaluate what the accessible literature can and cannot establish about the therapeutic role of herbal interventions in this syndrome, and to explain why an expanding volume of publication has not translated into greater certainty. Peer-reviewed evidence identified through eight open scholarly indexes was appraised with attention to design adequacy, outcome selection, risk of bias, consistency and reporting completeness. Mechanistic work is extensive and internally coherent, converging on insulin sensitisation, modulation of steroidogenic enzyme activity and androgen bioavailability, neuroendocrine effects on gonadotrophin secretion, and attenuation of oxidative and inflammatory signalling, with growing interest in the intestinal microbiota as an intermediary. Clinical corroboration is far weaker than the mechanistic literature implies. Reproducible signals exist for modest reductions in body weight, fasting glucose and insulin resistance indices with several botanicals, and for improved ovulation and pregnancy rates when multi-herb formulae are added to ovulation induction. Effects on androgen concentrations, hirsutism and menstrual regularity are inconsistent, and live birth is almost never reported. Certainty is limited by small samples, short exposure, open-label designs, surrogate endpoints, incomplete intervention characterisation, geographically concentrated trial populations, near-absent adverse event monitoring and demonstrable publication and language bias. Product quality, adulteration, heavy metal contamination and pharmacokinetic interaction are documented hazards that trial reporting rarely addresses. Herbal therapy in this syndrome is best characterised as biologically plausible and possibly useful as an adjunct for metabolic features, but not yet established for the reproductive and dermatological outcomes that matter most to patients. Progress requires adequately powered, placebo-controlled, chemically characterised trials reporting core outcomes and systematic safety data.